Przyczyny zmian jakościowych we wskaźniku bieżącym płynności finansowej - Szpulak, Aleksandra (Reasons of Quality Changes in the Current Ratio of Financial Liquidity, 2006)
As research of the corporate liquidity of Polish production companies shows, there were a lot of quality changes in the current ratio from 1995 to 2001. In this article the author presents their main reasons such as: payment block, financial restructurization and privatization through bankruptcy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 636-646